What environmental variables limit Typha expansion in Cape Flats wetlands? - Kilian, Kay-Leigh (Department of Biological Sciences, 2017)
The explosive expansion of Typha capensis into the wetlands of the Cape Flats has resulted in decreased species diversity and habitat value. Several initiatives to control this expansion have had varied success and management of wetlands dominated by T. capensis remains a challenge. For effective rehabilitation, one needs to understand what the problem is and its origin before any action can be taken. This study aims to determine whether there are any factors that limit the expansion of T. capensis that may be used in rehabilitation efforts, with the hypothesis being that the distribution of T. capensis is determined primarily by hydrology, salinity and nutrients such that wetlands with T. capensis or specific T. capensis stands will have stable hydrological regimes, moist soils, low salinities and high nutrients. Six wetlands in Rondevlei with varying dominance of T. capensis, ranging from not having any to being dominated by the plant, were examined. Wetlands were classified into types depending on their dominance of T. capensis, with Typha dominant, Mixed and No Typha wetland types. In each wetland soil cores were taken to represent the main vegetation types, focusing on T. capensis, Ficinia nodosa and Isolepis rubicunda. These three species comprise the dominant species of the three vegetation types that were measured, with T. capensis forming its own group and then rush-like and mat-like vegetation types respectively. Environmental variables like hydrology were observed by field visits at the end of summer and in winter/spring, and the soils were analyzed in the laboratory for salinity, pH and nutrients.